UJI AKTIVITAS IMUNOGLOBULIN M (IgM) EKSTRAK ETANOL HERBA RUMPUT MUTIARA (Hedyotis corymbosa) PADA MENCIT (Mus musculus) JANTAN DENGAN METODE HEMAGLUTINASI - Safriani Rahman; Bayu Putra; Rachmat Kosman; Riska Mustika (Fakultas Farmasi UMI, 2012)
A Research About Activity of Ethanol of Pearl Grass (Hedyotis corymbosa) On The Imunoglobulin M (IgM) by Hemaglutination Method Had Been Conducted of Male Mice. This research purpose to established of activity imunoglobulin M (IgM) from ethanol extract of pearl grass (Hedyotis corymbosa). Mice is animal that used for this research,The mice was divided into 4 treatment groups, where each group consisted of 3 mice. The first group as negative control, and each group was given Sheel Red Blood Cell (SRBC) 2 % as many 0,1 ml intraperitonially, after that negative control group was administrated with air sulingt, and other group was administrated with ethanol extract dose 26 mg, 78 mg, dan 130 mg for five days. The blood from all group was collected by intracardial after five days. The activity of imunoglobulin M (IgM) was measured by hemaglutination method based on titer of the imunoglobulin M (IgM) there was highest dilution of mice blood serum in which aglutination was showed. Research result showed Ethanol extract of Pearl Grass (Hedyotis corymbosa) at 26 mg, 78 mg, and 130 mg dose, can increased imunoglobulin M (IgM) activity.Key words : Imunoglobulin M, Hedyotis corymbosa, Hemaglutination Method